Paleoecology explains Holocene chemical changes in lakes of the Nhecolândia (Pantanal-Brazil) - Guerreiro, Renato Lada; McGlue, Michael M.; Stone, Jeffery R.; Bergier, Ivan; Parolin, Mauro; da Silva Caminha, Silane A. F.; Warren, Lucas V. [UNESP]; Assine, Mario L. [UNESP] (Springer Nature, 2018)
The objective of this research is to examine the history of lentic ecosystem salinity in the southern Pantanal wetlands (Brazil). The timing and controls on hydrochemical changes were inferred using sponge spicule and diatom paleoecology on a Holocene-aged sediment core from Nhecolândia, a lake district situated on a fossil lobe of the Taquari megafan. The oldest portion of the core contains Heterorotula fistula spicules, indicative of an ephemeral freshwater lake that existed until ~ 4.6 cal ka BP. Benthic diatoms of the genus Gomphonema and Eunotia appeared ~ 3.2 cal ka BP, indicating a shallow and dystrophic environment. A transition to a more permanent lake that hosted freshwater sponges (e.g., Corvoheteromeyenia spp.), and diatom assemblages (e.g., Cyclotella meneghiniana, Aulacoseira pantanalensis) endured until ~ 1.3 cal year BP; after this time, most sponges and planktic diatoms disappear from the sedimentary record. High abundances of Anomoeoneis sphaerophora and Craticula guaykuruorum in the latest Holocene reflect a transition to a hyperalkaline, saline lake environment. The results suggest that Nhecolândia’s saline lakes may evolve from freshwater precursors due to local (biochemical) and regional (geo-climatic) controls on water availability, which has implications for patterns of biodiversity and ecosystems services in Pantanal.
Keywords: Diatoms; Paleolimnology; Pantanal wetlands; Saline lakes; Sponge spicules